Lost and Found: Intimacy and Distance in Three Motherhood Memoirs about Autistic Children - Robertson, Rachel (Demeter Press, 2013)
This chapter explores the complexities of maternal representations of autistic children through an analysis of the play of intimacy and distance within three book-length memoirs. Robertson examines how mothers write about their child’s neurological difference whilst also representing the feelings of loss that such a difference may provoke. She compares the paradigms for understanding disability evident in each text, and suggests that the socio-cultural paradigm allows for a construction of disability that is progressive and sophisticated. Reflecting also on the author’s own lived experience of mothering an autistic child, this chapter shows the limitations within some current motherhood memoirs and points to new directions for the genre.